Diversity in Saccharum germplasm in Arunachal Pradesh, India - Nair, N.V.=700 1 Vigneswaran, M.
(En, Fr, Es)
ilus., 5 ref.
Keywords: ERIANTHUS; CONSERVACION DEL GERMOPLASMA; SACCHARUM; VARIACION GENETICA; INDIA